RANCANGAN FORMULIR DAN INSTRUKSI KERJA REGISTRASI JENAZAH FORENSIK DI RSUP DR. SARDJITO - , DHESMA ANESTY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The needs of the hospital for information and documentation concerning of the forensic corpse. Based on the observations and the results of the interview obtained data that information and documentation upon registration the forensic corpse at RSUP Dr. Sardjito less fulfilled resulting in less effective because they have not form registration forensic corpse and job instruction in filling form a registrar. Purpose: Designing form registration corpse forensic to answer the needs of format registration corpse forensic simple design in accordance with the standards with regard to physical aspects, aspect anatomik and aspects of content, and suits the needs of state services in installation of forensic at RSUP Dr. Sardjito. Designing a job instruction for filling the registration form on the forensics corpse of Dr Sardjito in accordance with the format process needs of the field. The Design Process : forms that are documented, the Books Registration Office in the installation of forensic, the results of observations, interviews, and theories that support made reference to designing corpse forensic registration form. The designer will make 3 draft form that will be presented, and then made the election so get the selected alternative design, consider the presence of input and output forms for items after it will make the selected alternative embodiment. The selected form is discussed to the user to obtain information on the procedures for charging. As a basis for making job instruction. Draft results: alternative 1 registration form bodies elected by focusing forensic detail and according to users ' needs, with a design that is easier in terms of filling, better views. The contents registration form consists of data corpse, information corpse, data preface, data receiver, data family of corpse, investigators, data examination, list of completeness letter. For the proposed work instructions charging corpse forensic registration form in accordance with the circumstances made the registration of the corpse.